Comparison of neonatal outcomes following progesterone use during ovarian stimulation with frozen-thawed embryo transfer - Xiuxian Zhu (Nature Portfolio, 2017)
Abstract Progesterone soft capsules (brand name: Utrogestan) were demonstrated to be an effective oral alternative to prevent premature LH surges both in normal-ovulatory and polycystic ovarian syndrome (PCOS) patients. However, its safety in terms of neonatal outcomes is unclear. To evaluate whether Utrogestan use increase the risk of adverse neonatal outcomes compared with short protocol in patients undergoing IVF/ICSI treatments in combination with frozen-thawed embryo transfer (FET), we performed a retrospective analysis including 1008 FET cycles, with embryos originated from either Utrogestan + hMG protocol (n = 499), or short protocol (n = 509), which led to 546 live-born infants. The neonatal characteristics regarding preterm birth (PTB), low birth weight (LBW), gestational age and mode of delivery were comparable in the two groups. The incidence of live-birth defect was 0.68% (2/293) in the Utrogestan + hMG protocol compared with 0.79% (2/253) in the short protocol. No early neonatal death or intrauterine death were recorded in either group. To date, the data do not indicate an elevated rate of abnormality at birth after progesterone use during ovarian stimulation but further study with larger populations is needed to confirm these results.